Effect of high hydrostatic pressure on the profile of proteins extracted fromBetula pendulapollens - Altuner, Ergin Murat; Çeter, Talip; Alpas, Hami (Informa UK Limited, 2014)
High hydrostatic pressure (HHP) has high success potential in pollen protein extraction, but its effect on pollen protein profiles has not been studied yet. The aim of this study is to put forward whether HHP processing causes a change in the protein profiles extracted from pollens or not. In this study, proteins extracted from Betula pendula pollens were studied at 100, 200 and 300 MPa at room temperature for 5 min. In addition, the efficiency of three different extraction solvents, namely phosphate buffer saline (PBS) buffer pH 7.5, trichloroacetic acid–acetone and Tris–HCl buffer pH 8.8, was also observed, and the results were compared with the conventional pollen protein extraction procedure. As a result, it is concluded that 200 MPa for 5 min has extracted similar amounts of protein compared with the conventional extraction method which lasted for 24 h, which lasted for 24 h. On the other hand, the application time for 200 MPa for 5 min is extremely shorter when it is compared to the conventional ext...
Keywords: 13. Climate action; 3. Good health